2008
DOI: 10.1152/ajpregu.00840.2006
|View full text |Cite
|
Sign up to set email alerts
|

Small-conductance, Ca2+-activated K+ channel 2 is the key functional component of SK channels in mouse urinary bladder

Abstract: -activated K ϩ (SK) channels play an important role in regulating the frequency and in shaping urinary bladder smooth muscle (UBSM) action potentials, thereby modulating contractility. Here we investigated a role for the SK2 member of the SK family (SK1-3) utilizing: 1) mice expressing ␤-galactosidase (␤-gal) under the direction of the SK2 promoter (SK2 ␤-gal mice) to localize SK2 expression and 2) mice lacking SK2 gene expression (SK2 Ϫ/Ϫ mice) to assess SK2 function. In SK2 ␤-gal mice, UBSM staining was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…As shown here, the pharmacological activation of the DSM SK channels further facilitates this physiological process. Our findings on the pharmacological activation of the SK channel in DSM are in line with previous studies using conditional and conventional SK2 and SK3 channel knockout mouse models (Herrera et al, 2003;Thorneloe et al, 2008). Selective SK3 channel overexpression reduces DSM spontaneous phasic contraction frequency and increases bladder capacity, whereas selective suppression of SK3 channel expression results in DSM overactivity (Herrera et al, 2003).…”
Section: Ska-31 Controls Detrusor Function 121supporting
confidence: 90%
See 2 more Smart Citations
“…As shown here, the pharmacological activation of the DSM SK channels further facilitates this physiological process. Our findings on the pharmacological activation of the SK channel in DSM are in line with previous studies using conditional and conventional SK2 and SK3 channel knockout mouse models (Herrera et al, 2003;Thorneloe et al, 2008). Selective SK3 channel overexpression reduces DSM spontaneous phasic contraction frequency and increases bladder capacity, whereas selective suppression of SK3 channel expression results in DSM overactivity (Herrera et al, 2003).…”
Section: Ska-31 Controls Detrusor Function 121supporting
confidence: 90%
“…In guinea pig and mouse DSM, SK channel inhibition increases the spontaneous phasic contraction amplitude and decreases the contraction frequency (Herrera et al, 2000(Herrera et al, , 2003Imai et al, 2001;Thorneloe et al, 2008). A recent report indicated that NS4591, an activator of SK/IK channels, inhibits EFS-and carbachol-induced contractions in rat, pig, and human DSM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated the expression of IK as well SK1, SK2, and SK3 in rat DRG neurons, including in putative nociceptive neurons (Mongan et al, 2005). Studies on mice with altered levels of SK2/SK3 expression have supported a role for both SK2 and SK3 in bladder control Thorneloe et al, 2008). However, in these mouse studies SK2 was shown to be expressed in smooth muscle cells, but not in the urothelium, whereas SK3 expression was observed in bladder smooth muscle and urothelium, but neither in afferent nor efferent nerves as evaluated by immunohistochemical costainings with neuronal markers.…”
Section: Discussionmentioning
confidence: 97%
“…In mice with conditionally suppressed SK3 expression , an involvement of SK3, and possibly other SK forms, in mouse bladder contractility was shown in experiments on bladder strips as well as by in vivo cystometry. Later, when SK2-deficient mice were analyzed, an important role for SK2 in regulation of detrusor contractibility was demonstrated (Thorneloe et al, 2008). The SK2 subunit was shown to be required for the apamin-sensitive regulation of bladder smooth muscle; however, both the actual SK channel composition in detrusor smooth muscle cells and possible species differences still remain to be further explored.…”
mentioning
confidence: 99%